Experimental study of temperatures in characteristic sections of the working zone of a closed two-phase thermosyphon under the condition of a heat removal by external periphery; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Nurpeiis А. Е. Atlant Ediluly (2017, 2017)
Title screen